2023
DOI: 10.3389/fnhum.2023.1152516
|View full text |Cite
|
Sign up to set email alerts
|

Speech rehabilitation in children with cochlear implants using a multisensory (French Cued Speech) or a hearing-focused (Auditory Verbal Therapy) approach

Abstract: IntroductionEarly exposure to a rich linguistic environment is essential as soon as the diagnosis of deafness is made. Cochlear implantation (CI) allows children to have access to speech perception in their early years. However, it provides only partial acoustic information, which can lead to difficulties in perceiving some phonetic contrasts. This study investigates the contribution of two spoken speech and language rehabilitation approaches to speech perception in children with CI using a lexicality judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Our results are coinciding with the results of Ertmer and Goffman [24] who found that the expressive skills were not significantly improved for prelingual children after one year of post cochlear implantation therapy. Furthermore Van Bogaert el al [25] displayed that auditory verbal therapy post cochlear implantation considered basic requirement for children's language development, they found that children with CI who enrolled in an auditory-focused speech rehabilitation approach showed significant improvement of their speech perception performance. The advantage of appropriate duration of auditory and speech therapy after cochlear implantation in improving hearing and oral communication was emphasized by other authors [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are coinciding with the results of Ertmer and Goffman [24] who found that the expressive skills were not significantly improved for prelingual children after one year of post cochlear implantation therapy. Furthermore Van Bogaert el al [25] displayed that auditory verbal therapy post cochlear implantation considered basic requirement for children's language development, they found that children with CI who enrolled in an auditory-focused speech rehabilitation approach showed significant improvement of their speech perception performance. The advantage of appropriate duration of auditory and speech therapy after cochlear implantation in improving hearing and oral communication was emphasized by other authors [26].…”
Section: Discussionmentioning
confidence: 99%
“…But some studies have also demonstrated longer-term benefits of a Cued Speech education: children who have been exposed to Cued Speech have better performance to phonological awareness tasks than their peers (e.g. Charlier & Leybaert, 2000;LaSasso et al 2003), and better performance to audio-only speech perception tasks (Kos et al, 2009;Van Bogaert et al, 2023). The hypothesis explored in this paper is that Cued Speech education provides children with hearing impairment with better phonological representations, which will translate into better speech production skills.…”
Section: Introductionmentioning
confidence: 90%
“…To that aim, phoneme and cluster accuracy in French children with cochlear implants is compared across different levels of Cued Speech proficiency. As suggested by Colin et al (2015;2017), and more recently Van Bogaert et al (2023), the child's individual ability to decode manual cues (i.e. Cued Speech proficiency) is a key factor when studying the effects of Cued Speech exposure.…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation